The effect of dental gel with IL-1β antagonist on indicators of nitrosative stress and antioxidant system in rats with experimental chronic generalized periodontitis - Dmytriieva, O. O.; Bielenichev, I. F.; Samura, I. B.; Salnykov, V. I.; Robota, D. V.; Дмитрієва, О. О.; Бєленічев, Ігор Федорович; Самура, Ірина Борисівна; Сальников, Валерій Ігорович; Робота, Дмитро Вадимович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the study was to evaluate the action of dental gel with IL-1β receptor antagonist on the indicators of nitrosative stress and antioxidant system in rats with experimental chronic generalized periodontitis. Materials and methods. Experimental chronic generalized periodontitis (CGP) was modeled using a calcium-deficient peroxide diet with reduced masticatory function in Wistar rats weighing 190–220 g for 8 weeks. The studied pharmacological agents were administered within 30 days after the development of CGP: 1 % dental gel with IL-1β receptor antagonist (1 mg/kg, locally using a dispenser); and antioxidant Mexidol (250 mg/kg, intragastrically). To assess the condition of periodontal tissues, the levels of nitrotyrosine, iNOS, Cu/ZnSOD, and glutathione peroxidase-4 were determined by immunoenzymatic quantitative analysis; levels of stable metabolites of NO, reduced and oxidized glutathione were determined using biochemical methods. Results. Course administration of dental gel with IL-1β antagonist in a therapeutic regimen to rats with CGP resulted in a decrease in the depth of periodontal pockets, almost complete elimination of bleeding and swelling of the gums, as well as to a decrease in iNOS expression by 37.8 % (p < 0.05), nitrotyrosine concentration – by 55.2 %, and NO metabolites – by 30 % (p < 0.05) in the blood of animals. Dental gel with IL-1β antagonist application resulted in an increase in concentration of reduced glutathione by 63 % (p < 0.05), glutathione peroxidase-4 expression – by 60.4 % (p < 0.05), and Cu/ZnSOD – by 31.2 % (p < 0.05) in the blood of animals with CGP. Mexidol, when administered to rats with CGP, affected only two studied indices – the level of nitrotyrosine and reduced glutathione (p < 0.05). However, it was inferior to the gel with the IL-1β receptor antagonist in terms of the degree of influence on these parameters (р < 0.05). Conclusions. The obtained results provide experimental justification for further study of IL-1β antagonist as a promising agent for the treatment of CGP. Мета роботи – оцінити вплив гелю стоматологічного з рецепторним антагоністом IL-1β на показники нітрозативного стресу й антиоксидантну систему в щурів з експериментальним хронічним генералізованим пародонтитом. Матеріали і методи. Експериментальний хронічний генералізований пародонтит (ХГП) відтворювали у щурів лінії Вістар масою 190–220 г за допомогою перекисної кальцій-дефіцитної дієти зі зниженою жувальною функцією протягом 8 тижнів. Фармакологічні агенти вводили протягом 30 діб після формування ХГП: 1 % гель стоматологічний із рецепторним антагоністом IL-1β (1 мг/кг) – місцево за допомогою дозатора; антиоксидант мексидол (250 мг/кг) – внутрішньогастрально. Для оцінювання стану тканин пародонта методом імуноферментного аналізу визначили рівні нітротирозину, iNOS, Cu/ZnSOD, глутатіонпероксидази-4 (GPx4); за допомогою біохімічних методів встановили рівні стабільних метаболітів NO, відновленого та окисненого глутатіону. Результати. Курсове введення гелю стоматологічного з антагоністом IL-1β у лікувальному режимі щурам із ХГП призвело до зменшення глибини пародонтальних кишень, майже повного усунення кровоточивості та набряку ясен, а також до зниження експресії iNOS на 37,8 % (p < 0,05), концентрації нітротирозину – на 55,2 %, NOх – на 30,0 % (p < 0,05) у крові тварин. Стоматологічний гель з антагоністом IL-1β підвищив концентрацію відновленого глутатіону на 63,0 % (p < 0,05), експресію GPx4 – на 60,4 % на (p < 0,05), Cu/ZnSOD – на 31,2 % (p < 0,05) у крові тварин із ХГП. Мексидол при введенні щурам із ХГП впливав тільки на рівні нітротирозину та відновленого глутатіону (р < 0,05). Однак за ступенем впливу на ці показники він поступався гелю з рецепторним антагоністом IL-1β (р < 0,05).
Вплив стоматологічного гелю з антагоністом IL-1β на показники нітрозативного стресу й антиоксидантну систему в щурів з експериментальним хронічним генералізованим пародонтитом
Dmytriieva O. O. - ORCID ID: 0009-0003-5259-2212; Bielenichev I. F. - ORCID ID: 0000-0003-1273-5314; Samura I. B. - ORCID ID: 0000-0001-5352-3209; Salnykov V. I. - ORCID ID: 0009-0002-9199-2174; Robota D. V. - ORCID ID: 0000-0003-2205-3579.
Keywords: chronic periodontitis; IL-1β receptor antagonist; dental gel; nitrosative stress; хронічний генералізований пародонтит; антагоніст рецепторів IL-1β; гель стоматологічний; нітрозативний стрес